Capacitance measurements of exocytosis in mouse pancreatic alpha-, beta- and delta-cells within intact islets of Langerhans. - Göpel, S; Zhang, Q; Eliasson, L; Ma, X; Galvanovskis, J; Kanno, T; Salehi, A; Rorsman, P (2004)
Capacitance measurements of exocytosis were applied to functionally identified alpha-, beta- and delta-cells in intact mouse pancreatic islets. The maximum rate of capacitance increase in beta-cells during a depolarization to 0 mV was equivalent to 14 granules s(-1), <5% of that observed in isolated beta-cells. Beta-cell secretion exhibited bell-shaped voltage dependence and peaked at +20 mV. At physiological membrane potentials (up to approximately -20 mV) the maximum rate of release was approximately 4 granules s(-1). Both exocytosis (measured by capacitance measurements) and insulin release (detected by radioimmunoassay) were strongly inhibited by the L-type Ca(2+) channel blocker nifedipine (25 microm) but only marginally (<20%) affected by the R-type Ca(2+) channel blocker SNX482 (100 nm). Exocytosis in the glucagon-producing alpha-cells peaked at +20 mV. The capacitance increases elicited by pulses to 0 mV exhibited biphasic kinetics and consisted of an initial transient (150 granules s(-1)) and a sustained late component (30 granules s(-1)). Whereas addition of the N-type Ca(2+) channel blocker omega-conotoxin GVIA (0.1 microm) inhibited glucagon secretion measured in the presence of 1 mm glucose to the same extent as an elevation of glucose to 20 mm, the L-type Ca(2+) channel blocker nifedipine (25 microm) had no effect. Thus, glucagon release during hyperglycaemic conditions depends principally on Ca(2+)-influx through N-type rather than L-type Ca(2+) channels. Exocytosis in the somatostatin-secreting delta-cells likewise exhibited two kinetically separable phases of capacitance increase and consisted of an early rapid (600 granules s(-1)) component followed by a sustained slower (60 granules s(-1)) component. We conclude that (1) capacitance measurements in intact pancreatic islets are feasible; (2) exocytosis measured in beta-cells in situ is significantly slower than that of isolated cells; and (3) the different types of islet cells exhibit distinct exocytotic features.